2023
DOI: 10.1002/advs.202207257
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lncRNA DDIT4‐AS1 Sensitizes Triple Negative Breast Cancer to Chemotherapy via Suppressing of Autophagy

Abstract: In this study, it is found that the lncRNA, DNA damage inducible transcript 4 antisense RNA1 (DDIT4-AS1), is highly expressed in triple-negative breast cancer (TNBC) cell lines and tissues due to H3K27 acetylation in the promoter region, and promotes the proliferation, migration, and invasion of TNBC cells via activating autophagy. Mechanistically, it is shown that DDIT4-AS1 induces autophagy by stabilizing DDIT4 mRNA via recruiting the RNA binding protein AUF1 and promoting the interaction between DDIT4 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Next, we investigated how the neddylation signal affected the sensitivity of PTX. We noticed that PTX has been reported as an inducer of autophagy [ 19 ]. Autophagy is a conserved cellular process related to chemoresistance in breast cancer [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated how the neddylation signal affected the sensitivity of PTX. We noticed that PTX has been reported as an inducer of autophagy [ 19 ]. Autophagy is a conserved cellular process related to chemoresistance in breast cancer [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…DUSP1 exhibited notable differences in early prognosis, and patients owned poorer prognoses when showing higher expression of DUSP1. In a recent study, Jiang et al 37 demonstrated that lncRNA DDIT4‐AS1 recruits RNA‐binding protein AUF1 to facilitate the interaction between AUF1 and DDIT4 mRNA, thereby stabilizing DDIT4 mRNA and inhibiting the mTORC1 signaling pathway. It induces the regulation of autophagy in TNBC cells and promotes the proliferation, migration, and invasion of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage-inducible transcript 4 (DDIT4) is known as a DNA damage derivable transcript, which could be ampli ed in DNA damage [18,19] . Over the past decades, DDIT4 were reported involved in a handful of human cancer, including head and neck carcinoma cancer, osteosarcoma, lung cancer, and breast cancer [20][21][22][23] . Recently, DDIT4 expression was uncovered highly expressed in OC cells and positively connected with patients' poor survival [24] .…”
Section: Discussionmentioning
confidence: 99%